2011
DOI: 10.1007/s00289-011-0663-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal polymerization of new polyimides with pendant phthalonitrile units

Abstract: New polyimides with pendant phthalonitrile units were synthesized via the conventional two-step polymerization approach. The chemical structure of the PIs was confirmed by IR and 1 H NMR spectra. The thermogravimetric analysis and differential scanning calorimetry revealed that the thermal properties of the new PIs along with their solvent-resistance can be promoted after thermal treatment at 300°C. This promotion can be attributed to the nitrile cure reaction of the phthalonitrile units indicated by the decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…However, some inherent limitations such as poor processability, brittleness and need for high curing temperature for long duration are to be overcome to effectively utilize the potential of phthalonitrile systems in engineering applications [8][9][10][11][12]. Many reports have revealed that the complete curing of the nitrile groups is practically impossible even after heating for long duration at elevated temperatures (300-350 °C) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, some inherent limitations such as poor processability, brittleness and need for high curing temperature for long duration are to be overcome to effectively utilize the potential of phthalonitrile systems in engineering applications [8][9][10][11][12]. Many reports have revealed that the complete curing of the nitrile groups is practically impossible even after heating for long duration at elevated temperatures (300-350 °C) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The ring-opening polyaddition reaction was performed at room temperature. In contrast, this reaction was conducted at higher temperature of 60°C using previously reported phthalonitrile-containing diamine, [22] due to its low reactivity, which can be probably attributed to the steric hindrance of the ortho-phthalonitrile unit. The lower polyaddition reactivity relative to that of CN-APB caused by steric hindrance can also be circumstantially evidenced by the difference of the chemical shift (NH 2 protons) in their 1 H NMR spectra, respectively, in the range 4.77-4.87 ppm for previously reported diamine and 5.04 ppm for CN-APB.…”
Section: Designed Monomers and Polymers 189mentioning
confidence: 93%
“…[20] In our previous study, phthalonitrile units were introduced as bulky pendant substituents into macromolecular system such as aromatic polyamide (CN-PA) [21] and polyimide (CN-PI). [22] The solubility of the polymers was improved, while their solvent-resistance and thermal properties can be controlled via the thermal polymerization of the pendant phthalonitrile groups. [21,22] The above-mentioned CN-PIs were synthesized from a designed phthalonitrile-containing diamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] Furthermore, 4-(4-vinylphenoxy) phthalonitrile is solid state at the preparation temperature. Thus we choose it as a representative solid functional vinyl monomer in this article.…”
Section: Introductionmentioning
confidence: 99%